2018
DOI: 10.3389/fnagi.2018.00414
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Derived Plasma Protein Biomarkers for Alzheimer’s Disease in Han Chinese

Abstract: It is well known that Alzheimer’s disease (AD) is one of the most common progressive neurodegenerative diseases; it begins gradually, and therefore no effective medicine is administered in the beginning. Thus, early diagnosis and prevention of AD are crucial. The present study focused on comparing the plasma protein changes between patients with AD and their healthy counterparts, aiming to explore a specific protein panel as a potential biomarker for AD patients in Han Chinese. Hence, we recruited and collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…In our results, 16 of the 30 hub genes are related to AZ. Among them, AGT, APOE, GJA1, MAOA, RAB31, NOTCH2, PDLIM5, SLC1A3, SMAD2, and YAP1 are biomarkers or related risk factors of AZ (Wu et al, 2004; Ueberham et al, 2009; Kanai et al, 2013; Cheng et al, 2018; Kajiwara et al, 2018; Liang et al, 2018; Quartey et al, 2018; Xu et al, 2018; Zhao et al, 2018). This further proves that there may be a certain relationship between BD and AZ, with overlapping mutant genes.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, 16 of the 30 hub genes are related to AZ. Among them, AGT, APOE, GJA1, MAOA, RAB31, NOTCH2, PDLIM5, SLC1A3, SMAD2, and YAP1 are biomarkers or related risk factors of AZ (Wu et al, 2004; Ueberham et al, 2009; Kanai et al, 2013; Cheng et al, 2018; Kajiwara et al, 2018; Liang et al, 2018; Quartey et al, 2018; Xu et al, 2018; Zhao et al, 2018). This further proves that there may be a certain relationship between BD and AZ, with overlapping mutant genes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in human and transgenic mouse models indicated that the plasma clusterin concentration was signi cantly increased in AD patients and was associated with the level of brillar Aβ in the brain. Moreover, plasma transthyretin levels were also signi cantly increased in comparisons between patients with AD and controls [36,68,69]. Aβ sequester proteins may have a dual function by reducing the formation of toxic species and increasing clearance and degradation through LRP-1-mediated endocytosis [21].…”
Section: Discussionmentioning
confidence: 96%
“…Proteomics is one of the most signi cant techniques that allows an extended investigation of neurodegenerative diseases. A blood-based proteomics approach was used extensively in humans with AD to study potential biomarkers or mechanisms related to this disease [36][37][38]. Proteomics in AD revealed many interesting proteins or pathways from CSF and blood, such as fatty acid oxidation and the advanced glycation end products/receptors for advanced glycation end products (AGE/RAGE) pathway [39,40].…”
mentioning
confidence: 99%
“…Plasma SAP levels are associated with Alzheimer’s disease in Han Chinese ( Cheng et al , 2018 ). However, that finding was age-adjusted and may not be relevant to Aging Proper.…”
Section: Discussionmentioning
confidence: 99%